DEEP NECK INFECTION ; A REPORT OF FIVE CASES - Akimoto, Rika; Baba, Syunkichi; Fujikura, Terumichi (JIBI INKOKA TEMBO, 1997)
From November 1995 to July 1996, we treated five patients with deep neck infection, containing two cases of gas gangrene. We also discussed recent 36 cases of deep neck infection including our 5 cases. Recent case reports of deep neck infection, especially cases of non-Clostridial gas gangrene, are increasing. For the treatment administration of antibiotics protecting against both aerobic and anaerobic bacterial infection is necessary. For example, administration of PIPC and CLDM is useful as the first choice. We treated 5 cases by administration of PIPC and CLDM, with surgical drainage for 3 cases. The appropriate therapy should be carried out quickly before the infection leads to a severe state and the planing of surgical drainage is also necessary at the same time. For the planing of surgical treatment CT scan is useful. Therefore if abscess formation is suspected CT scan should be done early without hesitations. Because the patients with deep neck infections often visit clinicians whose specialty is not otorhinolaryngology, the pathogenesis and severity should be discussed sufficiently with them. We have to care the cases which possibly lead to severe deep neck infections, such as the cases with diffuse neck swelling and redness, peri-tonsillitis, odontogenous infection, to prevent an increase in such cases.